PENERAPAN STRATEGI GENIUS LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA DI KELAS VII MTs. MUHAMMADIYAH SEI APUNG JAYA KECAMATAN TANJUNG BALAI KABUPATEN ASAHAN TAHUN PELAJARAN 2014/2015 - Mainur Nilawati (State Islamic University of North Sumatra, 2016)
The reseach was conducted Classroom Action Research (CAR) forincreasing a chievement student matematics and to know increasingstudent at MTs Muhammadiyah Sei Apung Jaya were class VII withusing genius learning strategy. Subject of this reseach was MTsMuhammadiyah Sei Apung Jaya student's Kecamatan TanjungbalaiKabupaten Asahan of class VII-A, the secod semester year student2014/2015 which consist of 46 student. Object of this reseach wasapplication genius learning strategi to increase achievement studentmatematics. Based on of achievement student matematics for materialgathering items before using genius learning strategy at class VII-AMTs Muhammadiyah Sei Apung Jaya student who got up 59, 22. Afterstudent was done learning with application genius learning strategy atthe first cycle, student got up 63,04% or 29 student and value was riseabout 71,5, and then the second cycle got up 86,96% or 40 student wirevalue 82,10. Based on of reseach that application of genius learningstrategy for increasing student matematics at class VII MTsMuhammadiyah Sei Apung Jaya Kecamatan Tanjugbalai KabupatenAsahan very effective was used to be able to increase student.